1993
DOI: 10.3109/01485019308988368
|View full text |Cite
|
Sign up to set email alerts
|

Semen Analysis in Insulin-Dependent/Non-Insulin-Dependent Diabetic Men with/without Neuropathy

Abstract: The present study deals with the diabetic neuropathies prevailing in the male population. In this investigation 100 insulin-dependent diabetes mellitus (IDDM) and 314 non-insulin-dependent diabetes mellitus (NIDDM) patients with and without an objective evidence of neuropathy, having an age span of 15 to 80 years and the duration of diabetes distributed over 1-33 years were included along with age-matched nondiabetic controls. The diabetic subjects were evaluated for semen analysis. Results of semen analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 18 publications
2
49
1
3
Order By: Relevance
“…[4,[25][26][27][28][29]30] Except significant decrease in sperm vitality all physical and microscopic parameters holds good with WHO [19] reference values in our study. This is the first report wherein except vitality; nil variation was observed in all other semen parameters in T2DM considering large sample size, unbiased sampling and confirmation done through 3 rounds of analysis.…”
Section: Discussionsupporting
confidence: 54%
“…[4,[25][26][27][28][29]30] Except significant decrease in sperm vitality all physical and microscopic parameters holds good with WHO [19] reference values in our study. This is the first report wherein except vitality; nil variation was observed in all other semen parameters in T2DM considering large sample size, unbiased sampling and confirmation done through 3 rounds of analysis.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, DM induces change in sperm count as well as sperm volume (Bartak et al, 1974). Some other studies have shown that the concentration and sperm count are increased in diabetics but that sperm motility and semen volume are decreased (Ali et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Ali and associates evaluated 314 men with NIDDM and neuropathy, they reported a higher sperm concentration and lower sperm motility compared with diabetic men without neuropathy and controls [23]. Though limited, these data suggest sperm dysfunction in some men with NIDDM.…”
Section: Diabetes and Infertilitymentioning
confidence: 99%